Constructing Ellipse Points as an Isometry of a Circle Using the Graphical Method - Akhmedov Nurali Odilovich (International Journal on Human-Computing Studies, 2024)
Creating ellipses dots from graphic method is offered in this article. In this case, the graphical method for constructing an ellipse is described in detail, and it is recommended to use it in modern architecture of buildings, since ellipsoids provide structural strength and have an excellent appearance.